PREPARASI KATALIS ABU KULIT KERANG UNTUK TRANSESTERIFIKASI MINYAK NYAMPLUNG MENJADI BIODIESEL (Preparation of Cockle Shell Powder Catalyst for Transesteriﬁcationof Calophyllumi inophyllum L. Oil to Biodiesel) - Zuhra Zuhra; Husni Husin; Fikri Hasfita; Wahyu Rinaldi (Agritech, 2015)
Biodiesel, as a potential substituted energy, has attracted a great attention in recent years, which can be produced from o3 renewable sources and provides complete combustion with less gaseous pollutant emission. Biodiesel is produced conventionally via transesteriﬁcation of vegetable oils using homogeneous catalysts, e.g. KOH, NaOH, and HaSO4. The homogeneous catalytic process, however, provides some disadvantages, such as, a huge production of wastewater from washing process of catalyst residues and non-reusability of the catalysts. In order to circumvent most of the economical and environmental drawbacks of homogeneous process, heterogeneous catalysts, this can be easily separated from reaction mixture by ﬁltration. These catalysts are less corrosive and more environment-friendly. The objective of this work was to develop the effectivity of using waste of cockle (Clinocardium nuttalli) shell as a heterogeneous base catalyst for the biodiesel production. The catalysts were prepared by simple calcination methods, at temperatures of 600, 700, 900 oC, and without calcination. Calcined catalysts were characterized by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM) technique. Transesteriﬁcation process of Calophyllum inophyllum L.oil and o methanol were carried out under bath reactor over the cockle shellcatalysts to produce biodiesel. The XRD patterns depicted that CaCO3 was successfully converted into CaO. SEM recorded demonstrates that the particle catalyst become smaller after heating. The highest activity was found at calcined catalyst of 900 oC, with the yield of biodiesel reaching 87.4% during 3 hours. The solid catalyst from waste cockle shell was proven to be durable for the transesteriﬁcation of edible oil.